(untitled) (Research, Society and Development, 2022)
As a result of the change in the pattern of atmospheric circulation caused by weather phenomena, in some areas of Brazil extreme droughts occur, in others, torrential rains. Such aspects make it possible to infer about the socio-environmental and economic problems resulting from these phenomena. In view of this, this work sought to analyze the relationship of El Niño Southern Oscillation (ENSO) events with rainfall anomaly index (IAC). The historical series of rainfall used were from the Santarém station (1969 to 2019) and Nova Maringá station (1984 to 2020), classifying the ENSO events within these periods, through the Niño Oscillation Index (ION). With this, it was observed from the IAC classification, that the strong phenomena as extremely dry and extremely humid, coincided with the classification of the ENSO phenomena of El Niño and La Niña for Santarém station. The El Niño and La Niña phenomena have little evident effect on the number of rainy days for the Maringá station. Through the study conducted to analyze the monthly and annual variations of rainfall through the IAC, it was shown that these occur in most cases under the influence of the more intense ENSO phenomenon, causing rain in that region. Comparing the results found for the south of the basin (Nova Maringá) and for the north (Santarém), it is observed that the influence of ENSO events is stronger for the northern region of the Tapajós River Basin (BHRT).